Roles of Staphylococcus aureus Mnh1 and Mnh2 Antiporters in Salt Tolerance, Alkali Tolerance, and Pathogenesis - Vaish, Manisha (J Bacteriol, 2018)
Staphylococcus aureus has three types of cation/proton antiporters. The type 3 family includes two multisubunit Na(+)/H(+) (Mnh) antiporters, Mnh1 and Mnh2. These antiporters are clusters of seven hydrophobic membrane-bound protein subunits. Mnh antiporters play important roles in maintaining cytoplasmic pH in prokaryotes, enabling their survival under extreme environmental stress. In this study, we investigated the physiological roles and catalytic properties of Mnh1 and Mnh2 in S. aureus. Both Mnh1 and Mnh2 were cloned separately into a pGEM3Z+ vector in the antiporter-deficient KNabc Escherichia coli strain. The catalytic properties of the antiporters were measured in everted (inside out) vesicles. The Mnh1 antiporter exhibited a significant exchange of Na(+)/H(+) cations at pH 7.5. Mnh2 showed a significant exchange of both Na(+)/H(+) and K(+)/H(+) cations, especially at pH 8.5. Under elevated salt conditions, deletion of the mnhA1 gene resulted in a significant reduction in the growth rate of S. aureus in the range of pH 7.5 to 9. Deletion of mnhA2 had similar effects but mainly in the range of pH 8.5 to 9.5. Double deletion of mnhA1 and mnhA2 led to a severe reduction in the S. aureus growth rate mainly at pH values above 8.5. The effects of functional losses of both antiporters in S. aureus were also assessed via their support of virulence in a mouse in vivo infection model. Deletion of the mnhA1 gene led to a major loss of S. aureus virulence in mice, while deletion of mnh2 led to no change in virulence. IMPORTANCE This study focuses on the catalytic properties and physiological roles of Mnh1 and Mnh2 cation/proton antiporters in S. aureus and their contributions under different stress conditions. The Mnh1 antiporter was found to have catalytic activity for Na(+)/H(+) antiport, and it plays a significant role in maintaining halotolerance at pH 7.5 while the Mnh2 antiporter has catalytic antiporter activities for Na(+)/H(+) and K(+)/H(+) that have roles in both osmotolerance and halotolerance in S. aureus. Study of S. aureus with a single deletion of either mnhA1 or mnhA2 was assessed in an infection model of mice. The result shows that mnhA1, but not mnhA2, plays a major role in S. aureus virulence.